Relationship between birth weight and ambient temperature during pregnancy in a cross-sectional study of the residents of Suzhou, China - Ding, Yi; Zhou, Hui; Tong, Min; Chen, Xiaofang; Zhao, Qian; Ma, Yuqin; Wu, Lei (Frontiers in Public Health, 2023)
Abstract Objective The association between birth weight and ambient temperature during pregnancy remains inconclusive, and data from Chinese populations are scarce. We conducted a cross-sectional study to investigate the association between birth weight and ambient temperature during pregnancy among the residents of Suzhou Industrial Park, Suzhou, China. Methods Information regarding 10903 infants born between January 2018 and December 2018 who were born at the hospitals in Suzhou Industrial Park, Jiangsu province was obtained via public birth records. Results This study found that the ambient temperature during the first trimester of pregnancy was negatively correlated with birth weight, suggesting that elevated temperature may be related to lower birth weight. However, the ambient temperatures during the second and third trimesters of pregnancy were positively correlated with birth weight. Moreover, when the ambient temperature was below 15°C during the second trimester of pregnancy, the birth weight increased with temperature. However, when the temperature was higher than 15°C, the birth weight decreased with temperature. The relationship between ambient temperature in the third trimester and birth weight presented an inverted "U" curve. When the ambient temperature was lower than 20℃, the birth weight increased with ambient temperature, but when the ambient temperature was higher than 20℃, the increase of ambient temperature showed no significant relationship with the increase of birth weight. And Conclusion The ambient temperature was correlated with birth weight. The ambient temperature during the first trimester of pregnancy was negatively correlated with birth weight. The relationship between ambient temperature in the third trimester and birth weight presented an inverted "U" curve.